SURVEY OF DENTAL SERVICES PROVISION TO PEOPLE WITH DISABILITIES IN GEORGIA - Samkharadze, Sopio; Osipova-Schoneich, Maia; Alkhanishvili, Zurab (European Scientific Journal, ESJ, 2014)
Access to dental care for people with disabilities is mostly related to various social and physical obstacles. The goal of this research is to study an overall situation of dental care access for persons with disabilities, follow up the factors influencing access to dental care for 15 nosologies. Qualitative and quantitative research methods were utilized. One hundred and forty two (142) dentists and residents (79% dentists and 21% resident dentists) were interviewed with self-administrated questionnaire. Research results demonstrate that 77% of persons with disabilities have applied for dental care at least once in their lifetime and mostly persons with Down syndrome have been refused to be served. According to the research results, treatment is most efficient in patients with diabetes, least efficient – in patients with cerebral palsy. The vast majority of the respondents wish to get more information on all 15 nosologies. Remarkably high interest was revealed towards autism, HIV/AIDS and hepatitis, the low interest – towards visual/hearing impairment. Research findings confirmed an obvious relation between being informed and readiness to provide dental service; moreover, the level of awareness on disability conditions is quite low. The attitudes to serve the persons with disabilities are tended to be negative. The lowest acceptance is demonstrated towards persons with Acquired Immune Deficiency Syndrome, AIDS. The study revealed the importance of revision of dental education modules on a higher education and post-diploma level in order to integrate several thematic issues with regard to disability and health conditions.